Ultrasound for diagnosis of birth weight discordance in twin pregnancies - Jahanfar, Shayesteh (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Diagnostic test accuracy). The objectives are as follows: Our primary objective is to determine the diagnostic accuracy (sensitivity and specificity) of different estimated biometric ultrasound measures using 30% thresholds with the actual birth weight discordance (BWD) as the reference standard (e.g. abdominal circumference (AC) compared with actual BWD) and to provide readers with a summary of the diagnostic accuracy of ultrasound measures for the diagnosis of BWD in twin gestations. 1. To assess the sensitivity and specificity of available diagnostic ultrasound tests in subgroups of twin pregnancies at various gestational ages by week (less than 28 weeks, 28 to 32 weeks, 32 to 36 weeks and more than 36 weeks). 2. To assess the sensitivity and specificity of each diagnostic ultrasound test in twin pregnancies with same‐sex versus opposite‐sex twins. 3. To assess the sensitivity and specificity of each diagnostic ultrasound test in dichorionic diamniotic versus monochorionic diamniotic twins. We anticipate the following potential sources of heterogeneity. 1. Clinical factors: characteristics of study population (gestational age, chorionicity, inclusion of high risk pregnancy complicated by underlying maternal‐fetal conditions, breast feeding). 2. Methodological factors: study design (patient selection, prospective versus retrospective studies, time of test performance (time between index test and reference standard), clinical settings (tertiary centre versus community health care), multiple testing versus single testing for diagnosis of high risk pregnancy complicated by maternal‐fetal conditions). 3. Other factors: geographic area (high‐, middle‐ and low‐income countries), year of publication. We will try to address these issues based on the number of studies available. Furthermore, observer variability bias or bias related to interpretation of results cannot be formally assessed in the context of this review.